Utilization of Three Species of Mangrove Wood Branches for Briquettes and Its Preference as Alternative Solid Biofuel - Hardiansyah Tambunan; Arif Nuryawan; Apri Heri Iswanto; Mohammad Basyuni; Iwan Risnasari; Andi Hermawan; Bora Jeong (Journal of Sylva Indonesiana, 2024)
Wood briquettes - one of the biomass energies - were produced from three species of mangrove wood branches, namely mata buaya (Bruguiera sexangula), buta-buta (Excoecaria agallocha), and bakau minyak (Rhizophora apiculata) using three types of starch adhesives made from tapioca, maize, and potato. This study aimed to evaluate user preferences for the kind of fuel, and responses to acceptance of the use of briquettes, and to analyze the effect of attributes on interest in using wood briquettes from mangrove wood branches. Cylindrical briquettes were produced in dimensions of 3 cm diameter and 4 cm thickness. After obtaining all the data, variance analysis and chi-square analysis were conducted. Before conducting the preference survey, evaluations of calorific value and color performance were carried out. The wood briquettes of this study have a calorific value that has met the ISO 17225-3:2-2020 standard of class A2. Even though the three types of wood briquettes differ in their L* (brightness), a* (red/green), and b* (blue/yellow) values, each briquette has a neutral color. A survey was conducted on 60 respondents using a questionnaire to evaluate user preferences for the type of fuel, responses to acceptance of the use of briquettes, and the effect of attributes on interest in using wood briquettes from mangrove wood branches. The results showed that gas is still the most preferred fuel by respondents, with as many as 35 people (58.33%). Meanwhile, 54 respondents (90%) stated they would use wood briquettes. Wood briquettes made of Bakau minyak wood species were the most preferred, with as many as 28 people (46.67%). The chi-square analysis results suggested no relationship between the preference for using wood briquettes from mangrove wood branches and fuel attributes. Based on this study, wood briquettes of mangrove wood branches have the potential to be an alternative fuel as long as their availability is easy to obtain.